Green IS Adoption Through Academic Web Services: A UTAUT-Based Evaluation at Universitas Sebelas Maret - Rizqi Satya Haprabu; Puspanda Hatta; Endar Suprih Wihidayat (Research in Education, Technology, and Multiculture, 2026)
Digital academic services at universities do not automatically ensure environmentally responsible use, and the extent to which such platforms support sustainable digital practice remains underexamined in higher education. This study evaluates how university students' use of academic web services contributes to the adoption of Green Information Systems (Green IS) using the Unified Theory of Acceptance and Use of Technology (UTAUT) as the theoretical framework. A quantitative survey collected data from 210 undergraduate and vocational students across 15 faculties at Universitas Sebelas Maret (UNS) who actively use the SIAKAD, SPADA, and OCW web services. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with a Two-Stage Higher-Order Construct approach, in which Green IS was specified as a formative higher-order construct built from three lower-order dimensions: Paperless, Work Efficiency, and Green Awareness. Results show that Social Influence (β=0.378), Facilitating Conditions (β=0.289), and Performance Expectancy (β=0.218) significantly influenced Behavioral Intention, while Effort Expectancy (β=0.078, p = 0.275) likely reflected students' prior familiarity with digital technologies. Use Behavior was the strongest predictor of Green IS adoption (β=0.639), and the Behavior Intention→Use Behavior→Green IS mediation pathway was confirmed as the core adoption mechanism, indicating that intention drives the Green IS outcome primarily through sustained actual use. The Paperless dimension contributed only marginally, suggesting that paperless practice remains in the early stages of Green IS maturity among students. These findings indicate that Green IS adoption in mandatory-use academic settings is driven less by ease of use and more by social expectations, institutional facilitation, and consistent system usage. Universities seeking to advance sustainable digital practices should prioritize social influence-based institutional policies, such as normalizing paperless workflows through lecturer and institutional endorsement. Keywords: Green IS, UTAUT, PLS-SEM, Higher Education, Behavioral Intention, Use Behavior